1999
DOI: 10.1292/jvms.61.1281
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variation of the D4 Dopamine Receptor Polymorphic Region in Two Dog Breeds, Golden Retriever and Shiba.

Abstract: ABSTRACT. The D4 dopamine receptor (D4DR) polymorphic region, which is possibly related to the personality trait known as novelty seeking in humans, was examined in 34 dogs from two breeds (Golden retriever and the Japanese indigenous breed, Shiba) by the polymerase chain reaction (PCR), and the DNA sequences of each allele were determined. The polymorphic region of the dog D4DR gene was composed of 39-and 12-base pair (bp) units, and four alleles (A-D) were identified based on the number and/or order of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 15 publications
2
53
0
Order By: Relevance
“…Human DRD4 is polymorphic in terms of the repeat number of the 48-bp sequence in exon III (Van Tol et al, 1992) and it has been demonstrated that the DRD4 genotype is possibly related to personality known as novelty seeking Ebstein et al, 1996). We previously found that the DRD4 exon III region is also polymorphic in the dog (Canis familiaris) (Niimi et al, 1999;Niimi et al, 2001) and we reported polymorphisms between interand intra-species. In this study, we investigated the exon III in poultry but no polymorphism was found.…”
Section: Discussionsupporting
confidence: 50%
“…Human DRD4 is polymorphic in terms of the repeat number of the 48-bp sequence in exon III (Van Tol et al, 1992) and it has been demonstrated that the DRD4 genotype is possibly related to personality known as novelty seeking Ebstein et al, 1996). We previously found that the DRD4 exon III region is also polymorphic in the dog (Canis familiaris) (Niimi et al, 1999;Niimi et al, 2001) and we reported polymorphisms between interand intra-species. In this study, we investigated the exon III in poultry but no polymorphism was found.…”
Section: Discussionsupporting
confidence: 50%
“…It has been demonstrated that the DRD4 genotype is possibly related to the personality trait known as novelty seeking [1,2]. We reported previously that DRD4 is also polymorphic in the dog (Canis familiaris) [10] and seven alleles were identified based on the number and/or order of 39-and 12-bp sequences located in the homologous region of human DRD4 [12]. In addition, a distinct difference in allele frequency was observed in several dog breeds with different behavioral traits [7,12] and the DRD4 genotype may be related to certain behavioral characteristics (e.g.…”
mentioning
confidence: 86%
“…[142][143][144][145] Twentythree dog breed were studied for aggression, and association was observed between this trait and the exon III polymorphism. 142 In the genus Equus (horses), the DRD4 exon III region includes an 18-bp repeat unit and there are inter-and intra-species differences in the number of repetitions.…”
Section: Gene-environment Interactionsmentioning
confidence: 99%